Evaluation and validation of a patient-reported quality-of-life questionnaire for Parkinson's disease - Pantelis Stathis; George Papadopoulos (SpringerOpen, 2022)
Abstract Background Parkinson's disease (PD) is a chronic, progressive illness with a profound impact on the health-related quality of life (HRQoL). Disease-specific patient-reported HRQoL measures, such as PDQ-39 and its short version PDQ-8, are increasingly used in clinical practice to address the consequences of PD on everyday life. Due to limitations in the content, especially in non-motor symptoms and sleep disturbances of PDQ-8, PDQoL7, a 7-item, short-term, self-reported, PD-specific HRQoL questionnaire was developed. Methods A representative sample of 60 adults with idiopathic PD completed the PDQoL7 questionnaire and the existing validated PDQ-8 and EQ-5D-5L questionnaires (all in Greek). Results PDQoL7 summary index strongly correlated with PDQ-8 (rs = 0.833, P < 0.001) and EQ-5D-5L (rs =  − 0.852, P < 0.001). The correlation between PDQoL7 and EQ-5D-5L was statistically significantly stronger compared to PDQ-8 and EQ-5D-5L (rs =  − 0.852 vs rs =  − 0.789 respectively, P < 0.001). The internal consistency of PDQoL7 was not affected by item deletion (positive item to total correlations: 0.29-0.63). No redundant items (with inter-item correlation coefficients greater than 0.80) were identified. Cronbach's α for PDQoL7 was comparable to PDQ-8 (0.804 versus 0.799 respectively). As PDQoL7 had three-dimensional structure, omega coefficient analysis confirmed its reliability (omega total: 0.88; omega hierarchical: 0.58). Conclusions PDQoL7 is an acceptable, easy to use, valid and reliable tool for the determination of HRQoL in PD patients that is potentially more comprehensive than PDQ-8 based on the available evidence. PDQoL7 could allow for a more thorough evaluation of the impact of PD and contribute to guiding healthcare decisions. This will be confirmed in subsequent analysis on larger patient cohorts.